2009
DOI: 10.1590/s0104-66322009000200012
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Pt-Ni catalysts supported on usy zeolite for n-hexane isomerization

Abstract: -Isomerization of linear alkanes has had considerable importance for the refining industry because the isomers formed in this reaction have high octane number. Most works reported in the literature studied the use of bifunctional catalysts, i.e., ones that have acid sites and metallic sites. In this study, bifunctional monometallic (Ni or Pt) and bimetallic catalysts (Pt-Ni), using HUSY zeolite as the support, were prepared in order to verify the role of the metal content and composition on the catalytic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Nevertheless, these metallic particles could have been located within the mesopore channels which were created during the hydrothermal dealumination of the Y zeolite, or at the outer surface of the catalyst grains, as has been reported [40]. It has also been suggested that there are likely to be smaller metal particles inside the cavities which are not detectable by TEM [42,43]. It was observed that the average metallic particle size in the case of the 2 wt% Pt/350USY was unchanged by the deactivation reaction, which may indicate that no metal sintering occurred; however, this conclusion cannot be assured, as TEM was able to study only limited regions of the samples and consequently the results should be interpreted as mainly local [43].…”
Section: Optimisation Of Chelating Extraction Parametersmentioning
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, these metallic particles could have been located within the mesopore channels which were created during the hydrothermal dealumination of the Y zeolite, or at the outer surface of the catalyst grains, as has been reported [40]. It has also been suggested that there are likely to be smaller metal particles inside the cavities which are not detectable by TEM [42,43]. It was observed that the average metallic particle size in the case of the 2 wt% Pt/350USY was unchanged by the deactivation reaction, which may indicate that no metal sintering occurred; however, this conclusion cannot be assured, as TEM was able to study only limited regions of the samples and consequently the results should be interpreted as mainly local [43].…”
Section: Optimisation Of Chelating Extraction Parametersmentioning
confidence: 91%
“…Deactivation was also found to be very rapid for the monometallic catalysts containing Ni at 0.5, 1, 1.5 and 2 wt%. This behaviour may be explained in terms of the poor hydrogenating capacity of Ni compared to Pt [44], making it more difficult for the Ni atoms to be fully reduced, so that not enough Ni metallic sites were available to sustain the reaction, since the hydroisomerisation reaction includes a dehydrogenation step [40,42]. Therefore, selectivity to form the C7 isomers was lower than for the catalysts containing Pt, while higher cracked and cyclic product yields were obtained, which means that higher coke content was formed, possibly blocking and poisoning the active sites of the catalysts during the deactivation reaction.…”
Section: Optimisation Of Chelating Extraction Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence of advanced countries on petroleum products, especially gasoline and the outbreak of petroleum crises in the 1970 s due to the increasing and overcoming consumption on production and extraordinary rise in petroleum prices and its products, urged industrialized countries to deal with energy problem and take a different approach [1][2][3][4]. Undoubtedly, the importance of the strategic product, gasoline in terms of current conditions, quality and quantity dimensions is not covered on everyone with respect to the growing demand of the country and the growth of imports and further dependence and the spread of environmental pollution and the prevalence of various diseases caused by pollution and the low quality of existence gasoline [5][6][7]. One of the most important properties and quality features of a high quality gasoline product is also low levels of pollutants such as sulfur, benzene, and aromatic compounds such as sulfur, benzene, and aromatic compounds and lead and manganese particles from environmental standards, octane number of the fuel [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on Pt-Ni systems supported on H-USY zeolite and Beta zeolite [15][16][17][18] showed that these provided catalytic activities were higher than those of monometallic Pt catalysts.…”
Section: Introductionmentioning
confidence: 99%